Penerapan Metode EDAS Dengan Kombinasi Pembobotan Entropy Dalam Penentuan Kinerja Dosen Terbaik di Masa Pembelajaran Daring - Khairunnisa Khairunnisa; Mesran Mesran (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Educational activities have recently experienced many changes in the teaching and learning system which is carried out online due to the Covid-19 pandemic outbreak which has resulted in the government imposing various regulations, making it impossible for face-to-face learning to be carried out in the current conditions. Not many lecturers or teaching staff have experienced a decline in the quality of their performance resulting in reduced activity and discipline of a lecturer in disseminating the knowledge he has in the educational environment, so that teaching and learning activities are no longer creative and innovative. So the researchers researched and utilized decision support systems with the application of the Entropy method used to determine the level of importance of the criteria used in lecturer performance and the EDAS method to calculate and rank lecturer performance. The Entropy and EDAS methods can determine the level of importance of a criterion, while the EDAS method can rank based on predetermined alternatives and criteria. With a decision support system that applies a combination of the EDAS method with Etropy weighting, it is hoped that this system can assist in determining the best lecturer performance at Budi Darma University. According to the results of applying the EDAS method with a combination of the entropy method as its weighting, the best alternative chosen in determining the best lecturer performance during the online learning period at Budi Darma University is the A8 alternative with the best score of 1 with the names Mesran, S.kom, M. com. The results of this study show that the decision support system that has been built using the EDAS method with a combination of this Entropy weighting, can facilitate Budi Darma University in determining the best lecturer performance accurately, quickly, efficiently and objectively.